In-hospital and six-month outcomes of elderly patients undergoing primary percutaneous coronary intervention for acute ST-elevation myocardial infarction - Noohi, Fereydoon (ARYA Atheroscler, 2016)
BACKGROUND: Elderly patients constitute a rapidly growing proportion of the population, and hence the increasing rises in the number of patients with ST-segment-elevation myocardial infarction (STEMI). Primary percutaneous coronary intervention (PCI), which is now established as the preferred reperfusion strategy in STEMI patients, has been inadequately investigated in this high-risk group. The aim of the present study was to investigate the in-hospital and 6-month outcomes of primary PCI in elderly patients (≥ 75 years) with STEMI. METHODS: A total of 100 elderly patients with STEMI including those with cardiogenic shock were included. Primary PCI procedures were performed in a tertiary referral center between 2009 and 2014. In-hospital and 6-month outcomes of patients were recorded and analyzed. RESULTS: The average age of the patients was 79.6 ± 3.8 years (range = 75-90 years) and 27.0% were women. Cardiovascular risk factors and prior events were common. Nearly, half of the patients had three-vessel disease and the left anterior descending artery (LAD) was the most common infarct-related artery. The presence of cardiogenic shock but not the other variables was associated with less anatomic and procedural success (P < 0.001). It was also the major independent predictors of 6-month mortality in the patients aged ≥ 75 years, [hazard ratio (HR) = 8.02; 95% confidence interval (CI): 1.75-25.97, P < 0.001]. In-hospital mortality was 2.4% in the patients without and 83.0% in those with cardiogenic shock. CONCLUSION: Primary PCI in aged patients could be associated with low complication rates and improved survival if performed in high-volume centers with experienced operators. Considering the very high rate of mortality in patients with cardiogenic shock, there should be measures to treat these patients before the onset of hemodynamic instability.